IMPORTANCE OF NATIONAL AUDIOVISUAL NETWORKS IN THE DEVELOPMENT OF THE IMAGE OF THE COUNTRY (Scientific journal of the Fergana State University, 2023)
In the modern world, radio and television are of particular importance in building public relations. For this reason, it is necessary to carefully study the issue of the effective use of audiovisual networks to strengthen the image of the country. This article analyzes some issues related to the activities of leading television and radio channels in Uzbekistan.